The Hysterectomy Hoax / Stanley West - West, Stanley (New York (State) : Doubleday, 1994)
Trata de The Hysterectomy Hoax.
1. An intact woman 2. American way of hysterectomy
incluye índice
Col. Salud
Keywords: 1. ENDOMETRIOSIS 2. MORE ABOUT OVARIES